Perencanaan Search Engine E-commerce dengan Metode Latent Semantic Indexing Berbasis Multiplatform - Lestari, Ni Made Ari; Sudarma, Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 1 April 2017, 2017)
E-commerce is a sale and purchase transactions that occur through electronic systems such as the Internet, WWW, or other computer networks. E-commerce involves electronic data interchange and automated data collection systems. In all e-commerce search engine provided a column for the search items desired by the user. In e-commerce such as Tokopedia, Lazada, MatahariMall, Amazon, and other search engines that provided just use a regular search engine technology. In the usual search engines getting longer sentences from the input or output of goods search results will be more extensive and more. However, by utilizing the semantic indexing technology, the longer and clear input desired goods, the number of searches will be few and accurately in accordance with the input that helps the user in decision making.  In this study discussed how to build a search engine on the web e-commerce by using Latent Semantic Indexing. The first starts from the use of Text Mining methods for word processing, and the method Levenshtein Distance to repair automatic word and the last Latent Semantic Indexing for information processing and input expenditure.
Keywords: e-commerce; search engine; Latent Semantic Indexing; Text Mining; Levenshtein Distance